Immune response to the hepatitis B vaccine among HIV-infected adults in Uganda. Issue 8 (22nd February 2021) - Seremba, E.; Ocama, P.; Ssekitoleko, R.; Mayanja-Kizza, H.; Adams, S.V.; Orem, J.; Katabira, E.; Reynolds, S.J.; Nabatanzi, R.; Casper, C.; Phipps, W.
Abstract: Background: Co-infection with hepatitis B virus (HBV) and human immunodeficiency virus (HIV) is common in sub-Saharan Africa (SSA) and can rapidly progress to cirrhosis and hepatocellular carcinoma. Recent data demonstrate ongoing HBV transmission among HIV-infected adults in SSA, suggesting that complications of HIV/HBV co-infection could be prevented with HBV vaccination. Because HBV vaccine efficacy is poorly understood among HIV-infected persons in SSA, we sought to characterize the humoral response to the HBV vaccine in HIV-seropositive Ugandan adults. Methods: We enrolled HIV-infected adults in Kampala, Uganda without serologic evidence of prior HBV infection. Three HBV vaccine doses were administered at 0, 1 and 6 months. Anti-HBs levels were measured 4 weeks after the third vaccine dose. "Response" to vaccination was defined as anti-HBs levels ≥ 10 IU/L and "high response" as ≥ 100 IU/L. Regression analysis was used to determine predictors of response. Results: Of 251 HIV-positive adults screened, 132 (53%) had no prior HBV infection or immunity and were enrolled. Most participants were women [89 (67%)]; median (IQR) age was 32 years (27–41), and 68 (52%) had received antiretroviral therapy (ART) for > 3 months. Median (IQR) CD4 count was 426 (261–583), and 64 (94%) of the 68 receiving ART had undetectable plasma HIV RNA. Overall, 117 (92%) participants seroconverted to the vaccine (anti-HBs ≥ 10 IU/L), with 109 (86%) participants having high-level response (anti-HBs ≥ 100 IU/L). In multivariate analysis, only baseline CD4 > 200 cells/mm3 was associated with response [OR = 6.97 (1.34–34.71), p = 0.02] and high-level response [OR = 4.25 (1.15–15.69)], p = 0.03]. Conclusion: HBV vaccination was effective in eliciting a protective humoral response, particularly among those with higher CD4 counts. Half of the screened patients did not have immunity to HBV infection, suggesting a large at-risk population for HBV infection among HIV-positive adults in Uganda. Our findings support including HBV vaccination as part of routine care among HIV-positive adults.